2011
DOI: 10.2478/v10016-011-0002-9
|View full text |Cite
|
Sign up to set email alerts
|

Inferring Pragmatic Messages from Metaphor

Abstract: When speakers utter metaphors, such as "Lawyers are also sharks," they often intend to communicate messages beyond those expressed by the metaphorical meaning of these expressions. For instance, in some circumstances, a speaker may state "Lawyers are also sharks" to strengthen a previous speaker"s negative beliefs about lawyers, to add new information about lawyers to listeners to some context, or even to contradict a previous speaker"s positive assertions about lawyers. In each case, speaking metaphorically c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…The reconstruction of a minimal relevance relation (Macagno 2018) between the vehicle and the purpose of the utterance (Gibbs et al 2011) can explain the "strong implicatures" that metaphorical utterances license, but cannot explain fully the argumentative effects of some metaphors. The arguments that result from this level of understanding do not exhaust the argumentative effect of the metaphorical move: if the latter were only a strategy for expressing an argument that can be conveyed through non-metaphorical means, there wouldn't be much reason to use metaphor in the first place (Reinhart 1976: 392).…”
Section: Metaphors Communicate Argumentsmentioning
confidence: 99%
“…The reconstruction of a minimal relevance relation (Macagno 2018) between the vehicle and the purpose of the utterance (Gibbs et al 2011) can explain the "strong implicatures" that metaphorical utterances license, but cannot explain fully the argumentative effects of some metaphors. The arguments that result from this level of understanding do not exhaust the argumentative effect of the metaphorical move: if the latter were only a strategy for expressing an argument that can be conveyed through non-metaphorical means, there wouldn't be much reason to use metaphor in the first place (Reinhart 1976: 392).…”
Section: Metaphors Communicate Argumentsmentioning
confidence: 99%
“…We do not just comprehend metaphors to derive their metaphorical meanings, but interpret them to infer pragmatically relevant messages in different discourse contexts. For example, studies have demonstrated that people take more time to understand the metaphorical statement "My lawyer is also a shark" when that remark contradicted a previously stated belief (e.g., "Lawyers are always kind") than when the metaphor strengthened a previously stated idea (e.g., "Lawyers are persistent") (Gibbs et al, 2011). The total time to understand a metaphor incorporates our assessment of its validity and appropriateness in the context in which it appears.…”
Section: Resistance To Metaphors I N Experimentsmentioning
confidence: 99%
“…We often fail to appreciate people's pragmatic experiences of language in our quest to test specific hypotheses from linguistic pragmatics. To take one example, studies show that people take different times to interpret a metaphorical statement, such as "Lawyers are also sharks, " depending on whether that expression is intended to simply affirm a pre-existing belief in some discourse, add new information, or contradict a previously asserted belief (Gibbs et al, 2011). People do not simply understand a metaphor as only expressing a metaphorical meaning, but interpret it more precisely in terms of its specific pragmatic messages in context (e.g., that a speaker wishes to strengthen an existing assumption, add new information, or contradict a previously stated belief about some topic).…”
Section: The Superficiality and Richness Of Pragmatic Experiencementioning
confidence: 99%